Violeta Parra: Popular Educator - Maria A Vetter (Adult Education Research Conference, 2017)
This study reexamines the work of Chilean folklorist Violeta Parra with the purpose of identifying her as a popular educator.
Keywords: Violeta Parra; Folklore; Popular Education